A Teenager in Love: Multidimensional Human Capital and Teenage Pregnancy in Ghana - Niels-Hugo Blunch (Global Labor Organization (GLO), 2017)
I examine teenage pregnancy in Ghana, focusing on the role and interplay of Ghanaian and English reading skills, formal educational attainment, and adult literacy program participation. Pursuing several alternative identification strategies three main results are established. First, I confirm the finding from previous studies that educational attainment is negatively related to teenage pregnancy. Second, however, once Ghanaian and English reading skills are introduced, the association between educational attainment and teenage pregnancy decreases or disappears altogether. Third, for the girls who have not completed primary school, adult literacy program participation is associated with a much lower probability of experiencing a teenage pregnancy.
Keywords: I21; J24; 330; Teenage pregnancy; human capital; literacy; adult literacy programs; Ghana